2021
DOI: 10.1094/pdis-05-20-0977-re
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Phylogenetic Resolution of Diplodia corticola and D. quercivora, Emerging Canker Pathogens of Oak (Quercus spp.), in the United States

Abstract: In Mediterranean Europe and the United States, oak species (Quercus spp.) have been in various states of decline for the past several decades. Several insect pests and pathogens contribute to this decline to varying degrees including Phytophthora cinnamomi, Armillaria spp., various insect defoliators, and additionally in the U.S., the oak wilt pathogen, Bretziella fagacearum. More recently, two emerging canker pathogens, Diplodia corticola (Dc) and Diplodia quercivora (Dq) have been implicated in causing dieba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The presence of D. corticola, D. quercivora and Discula quercina in declining cork oak trees agrees with their role as emerging pathogens to Quercus spp. in different regions of the world [11,41], which is emphasized by their risk to cork oak health as previously reported [39,42]. Concerning the fungi displaying a beneficial role, AL forest presented the highest number of OTUs with a potential beneficial role (all described as pathogenic-beneficial), but GV forest was the richest with exclusive beneficial fungi (Figure 2A).…”
Section: Endophytic Fungal Community Of Cork Oaksupporting
confidence: 77%
“…The presence of D. corticola, D. quercivora and Discula quercina in declining cork oak trees agrees with their role as emerging pathogens to Quercus spp. in different regions of the world [11,41], which is emphasized by their risk to cork oak health as previously reported [39,42]. Concerning the fungi displaying a beneficial role, AL forest presented the highest number of OTUs with a potential beneficial role (all described as pathogenic-beneficial), but GV forest was the richest with exclusive beneficial fungi (Figure 2A).…”
Section: Endophytic Fungal Community Of Cork Oaksupporting
confidence: 77%
“…D. quercivora is recognized as a pathogen of Quercus spp. in other countries [29][30][31]37]. However, our study has shown that this species is also associated as a pathogen with holm oak in Italy.…”
Section: Discussionmentioning
confidence: 51%
“…In Italy, as well as in the rest of Europe, increasingly frequent reports of tree decline in oak forests have been recorded and a range of oak pathogens, for example, Armillaria spp., Cephalosporium spp., Cladosporium spp., Cylindrocarpon spp., Diplodia spp., Biscogniauxia mediterranea (Hypoxylon mediterraneum), Phoma cavae, Phomopsis quercina, Sporotrix spp., and Phytophthora spp. have been found to be associated with this decline [27][28][29][30][31][32][33][34]. It is not yet clear whether the disease development in many of these cases is primarily caused by emerging pathogens, as, for example, found in Italy for Diplodia corticola and Phytophthora cinnamomi on declining holm oak in Caprera Island (Sardinia) [28] and in the Salento Peninsula (Apulia) [35], or whether tree decline is due to physiological stresses caused by climate change, as in the case of the Lucanian Apennine (Basilicata Region) in Italy [36].…”
Section: Discussionmentioning
confidence: 93%
“…In this study, using the sequence data of act and tef1-α genes suggested by Urbez-Torres et al [39] improved the phylogenetic resolution of this species complex. This approach has also been extensively used to resolve phylogenies of other plant-associated fungal pathogens such as Diaporthe [71], Valsaria [72] and Diplodia [73].…”
Section: Plos Onementioning
confidence: 99%